Guarding Education for All: The Strategic Role of Madrasah Supervisory Supervision in Realizing Inclusive Madrasah - Abdul Hamid (JUMPA : Jurnal Manajemen Pendidikan, 2024)
This research focuses on the strategic role of madrasah supervisors in realizing inclusive education in madrasas in Krejengan, Kraksaan, Probolinggo. The main objective of this study is to explore how madrasah supervisors can optimize the use of technology and collaboration with religious leaders in supporting the implementation of inclusive policies. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, participatory observations, and document analysis from several madrasas at the research site. Data analysis was carried out using an interactive analysis model from Miles and Huberman, which included data reduction, data presentation, and conclusion drawn. The results show that the use of digital technology by madrasah supervisors significantly improves the efficiency of supervision and strengthens the relationship between supervisors, teachers, and students in the context of inclusive education. In addition, collaboration with religious leaders has proven effective in reducing stigma in society and increasing community support for inclusive programs. The implications of this study show that supervision strategies that integrate technology and community-based collaboration can be an effective model to be applied in other madrasas that face similar challenges. These results also emphasize the importance of developing more adaptive and evidence-based education policies in supporting inclusivity in the educational environment